(untitled) (Research, Society and Development, 2023)
Introduction: Individuals born with cleft palate may face a number of challenges, including anatomical deformities, dental malocclusion, hearing impairment and speech disorder. Those who develop maxillary hypoplasia may receive osteogenic distraction or later orthognathic surgery, which can reposition the maxilla to a functional and esthetic position. This surgical advancement of the maxilla has been reported for over 30 years. According to the ideal protocol, the lip should be operated from 3 months of age, in a procedure known as cheiloplasty, while 12 months is the time determined for palatoplasty. Objective: To review in the literature what would be the advantages and disadvantages of an early approach to an osteogenic distraction to the detriment of a subsequent orthognathic surgery in cleft patients. Methodology: It was carried out in the period between 2006 and 2019 through the databases: Science direct and Pubmed. Results: A total of 95 articles were found, 26 duplicates were excluded and 69 were selected for the survey. Conclusion: We can see that both surgeries have their benefits performed at the right times during the patient’s life, requiring multidisciplinary treatment with psychologists, doctors, speech therapists, among others. However, there is a bias of osteogenic surgery, as we do not always obtain an expected and objective result.